2006
DOI: 10.1002/sce.20162
|View full text |Cite
|
Sign up to set email alerts
|

Learning and teaching as emergent features of informal settings: An ethnographic study in an environmental action group

Abstract: Around the world, many people concerned with the state of the environment participate in environmental action groups. Much of their learning occurs informally, simply by participating in the everyday, ongoing collective life of the chosen group. Such settings provide unique opportunities for studying how people learn science in complex settings without being directly instructed. This study was designed to investigate learning and teaching that occurs through ordinary, everyday participation in environmental ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Interestingly, both interactive and social learning theories borrow terms from ecology, including references to learning as an emergent property arising out of interactions that are only partially controlled by the facilitator or teacher, and as fostering changes in the learner and the environment through a series of feedback loops and other interactions (Boyer and Roth 2006;Chawla 2008;Tidball and Krasny, 2009). Thus, an understanding of interactive and social learning is useful in considering how a civic ecology practice, such as community gardening, might foster outcomes not only for individuals, but also for the larger social-ecological system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both interactive and social learning theories borrow terms from ecology, including references to learning as an emergent property arising out of interactions that are only partially controlled by the facilitator or teacher, and as fostering changes in the learner and the environment through a series of feedback loops and other interactions (Boyer and Roth 2006;Chawla 2008;Tidball and Krasny, 2009). Thus, an understanding of interactive and social learning is useful in considering how a civic ecology practice, such as community gardening, might foster outcomes not only for individuals, but also for the larger social-ecological system.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their importance in adaptive co-management, social learning and social capital may enhance the resilience of a city neighborhood or other social-ecological system, or the capacity of such systems to respond to ongoing and catastrophic disturbances and conflict (Walker and Salt 2006). Boyer and Roth (2006) have differentiated between school classrooms and out-of-school "heterogeneous" learning environments, which because of their variable and changing cultural, bio-physical and social environment, offer multiple opportunities for learning not available in classrooms. Community gardens, with their diversity of plants, cultures, and management and governance practices, can be considered as heterogeneous learning environments offering multiple possibilities for learning focused on science, stewardship, and advocacy.…”
Section: Concerted Action: Social Learning Among Groupsmentioning
confidence: 99%
“…As the students in the structured groups had more opportunities to work together, they developed a stronger perception of group cohesion and social responsibility for each other's teaching (Gillies 2004). Educators should consider participating in lessons as facilitators rather than teaching directly and allowing their students to teach each other, because explaining a phenomenon to others leads the explainer to a deeper understanding of its nuances (Boyer and Roth 2006). Research literature has shown that to provide the best cooperative learning environment, students should be placed into heterogeneous groups of varying ability levels (Leikin and Zaslavsky 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Vygotsky (1962) suggested that the construction of new meanings takes place in a "zone of proximal development," or that area of cognitive structure that is prepared to accept new or altered ideas. This may account, in part, for the effectiveness of group learning, since students tend to be closely matched in their "zones of proximal development" and useful negotiation of meanings can occur between them as they learn from and teach one another as partners in environmental inquiry (Boyer and Roth 2006). The collaborative dialogue supports learning among students, helping them to clarify their thinking and to consolidate their ideas (Hmelo-Silver et al 2002).…”
Section: Collaborative Learningmentioning
confidence: 97%
“…Similar interactive notions of learning are described in the ecosystems management literature; for example PahlWostl (2006) states that social learning within the context of resource management ''assumes an iterative feedback between learners and their environment, i.e., the learner is changing the environment, and these changes are affecting the learner.'' Similarly, activity theory focuses attention on the transformations of individuals and their social and biophysical environment, which result from humans not merely reacting but also acting to change the conditions that mediate their activities (Engeströ m 2001, Boyer andRoth 2006, Krasny andRoth 2010). Activity theory suggests that learning emerges through interactions among six elements of an activity system: the subjects (participants), objects (e.g., garden or other ecosystem that is the focus of practice), community (participants and the wider community impacted by their work), tools (e.g., seeds), rules (e.g., allowing removal of invasive species but not of native species), and division of labor (roles of participants and other community members) (Engeströ m 1987).…”
Section: ) Civic Ecologymentioning
confidence: 99%